Capital Structure: Do Size And Profitability Of A Company Highly Affect Capital Structure? - Irdiana, Sukma (Jurnal Ilmu Manajemen Advantage, 2021)
The capital structure is a description of the form of the company's financial proportion. In realizing the optimal capital structure, financial managers must consider the factors that affect the capital structure. With the many factors that can affect the capital structure, the purpose of this study is to determine and analyze the size of the company against the capital structure with profitability as an intervening variable. The sampling technique used was purposive sampling, with a total sample size of 100 companies that met the criteria. The data analysis technique used is path analysis. The results of this study indicate that there is no direct relationship between company size and profitability. Meanwhile, company size and capital structure have a direct relationship. Likewise, profitability with capital structure has a direct relationship.